Effectiveness of Isotonic Beverages and Mineral Water Beverages to Recovery Time after Cooper Test - Edward Valentino Butar-Butar; Refi Ikhtiari; Ahmad Raif Martinus (International Journal of Health and Pharmaceutical (IJHP), 2022)
Exercise is one way that can be done towards a healthy life. When exercising the body will lose a lot of fluid in the form of electrolytes through sweat. Most people after exercise will consume mineral water which causes a decrease in the concentration of sodium in the blood plasma thus reducing thirst further delaying the rehydration process. Currently popular with isotonic beverages that have a similar osmolarity value of body fluids, and have the benefit of restoring lost body fluids so that the body avoids dehydration. This study aims to determine the effectiveness of isotonic drinks and mineral water to the recovery of physical exercise after conducting a Cooper Test. The method used is experimental research Pretest - posttest Control Group Design.